2018
DOI: 10.1007/s13224-018-1127-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Decubitus Ulcer on Cervix in Pelvic Organ Prolapse with POP-Q Staging

Abstract: Aim Utero vaginal prolapse is a very common complaint of patients in the OPD. It's an entity that existed since a very long time and hence many classifications were proposed; however, only one system was found to be a validated system for determining the degree of prolapse-POP-Q system. Objective To determine the relationship of decubitus ulcer with POP-Q staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Most of the cases neglected themselves and presented late with a higher stage of pelvic organ prolapse and a larger size of decubitus ulcer. A similar result has also been shown by Deshpande et al [ 18 ]. Deshpande et al also observed that as the measurement of point C increases, the area of decubitus ulcer also increases.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the cases neglected themselves and presented late with a higher stage of pelvic organ prolapse and a larger size of decubitus ulcer. A similar result has also been shown by Deshpande et al [ 18 ]. Deshpande et al also observed that as the measurement of point C increases, the area of decubitus ulcer also increases.…”
Section: Discussionsupporting
confidence: 90%